2001
DOI: 10.1002/cbm.397
|View full text |Cite
|
Sign up to set email alerts
|

What is problem solving? A review of theory, research and applications

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 95 publications
1
10
0
2
Order By: Relevance
“…Recent research has shown that the absence of effective problem-solving skills is associated with interpersonal difficulties, behavioural problems, negative affect and psychological adjustment (see Antonowicz & Ross, 2005;McGuire, 2001 for thorough reviews). Particularly relevant for this study is that offenders have been found to have less effective problem-solving abilities than other more well-adjusted groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that the absence of effective problem-solving skills is associated with interpersonal difficulties, behavioural problems, negative affect and psychological adjustment (see Antonowicz & Ross, 2005;McGuire, 2001 for thorough reviews). Particularly relevant for this study is that offenders have been found to have less effective problem-solving abilities than other more well-adjusted groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found (Friendship, Blud, Erikson, & Travers, 2002), and not found (Falshaw, Friendship, Travers, & Nupent, 2003), differences in reconviction rates for offenders who have been provided with ''thinking skills'' programs designed to tackle the perceived different patterns of problem solving. If these studies, perhaps after improvements in the programs devised (McGuire, 2001), do show that cognitive skills training can make a difference in terms of reconviction rates, then there are considerable implications for lawyers. It will be possible to devise more appropriate sentences.…”
Section: Mens Reamentioning
confidence: 96%
“…The average lengths of stay (at T1) of DBT-F-patients was significantly shorter than in the other groups (DBT-F versus R&R p = .014; versus TAU p = .048), but there was no difference between the R&R and the DBT-F group. The number of months at T1 varied from 2 (DBT-F group) to 18 (DBT-F and TAU) months, outliers (38,26, and 23 months) were removed.…”
Section: The Examined Samplementioning
confidence: 99%
“…The relationship between social problem-solving and criminal behavior has been thoroughly examined in the literature (37)(38)(39)(40)(41). Poor social problem-solving abilities have been hypothesized to lead to criminal behaviors as maladaptive attempts to solve personal or interpersonal problems (40).…”
Section: Introductionmentioning
confidence: 99%